R machine learning by example : understand the fundamentals of machine learning with R and build your own dynamic algorithms to tackle complicated real-world problems successfully /: understand the fundamentals of machine learning with R and build your own dynamic algorithms to tackle complicated real-world problems successfully. (2016) - Bali, Raghav; Sarkar, Dipanjan
No abstract available